The effect of subcutaneous and sublingual birch pollen immunotherapy on birch pollen–related food allergy: a systematic review - Kallen, E. J. J.; Welsing, P. M. J.; Löwik, J. M.; Van Ree, R.; Knulst, A. C.; Le, T. M. (Frontiers in Allergy, 2024)
Background Birch pollen–related food allergy (BPFA) is the most common type of food allergy in birch-endemic areas such as Western and Central Europe. Currently, there is no treatment available for BPFA. Due to the cross-reactivity between birch pollen and a range of implicated plant foods, birch pollen allergen immunotherapy (AIT) may be effective in the treatment of BPFA. In this study, we systematically evaluate the effectiveness of birch pollen–specific subcutaneous or sublingual immunotherapy in treating BPFA. Methods A search was performed in the PubMed, Embase, and Cochrane libraries. Studies were independently screened by two reviewers against predefined eligibility criteria. The outcomes of interest were changes in (1) severity of symptoms during food challenge, (2) eliciting dose (ED), and (3) food allergy quality of life (FA-QoL). The validity of the selected articles was assessed using the revised Cochrane risk of bias tool. We focused on studies with the lowest risk of bias and considered studies with a high risk of bias as supportive. Data were descriptively summarized. Results Ten studies were selected that included 475 patients in total. Seven studies were categorized into “high risk of bias” and three into “moderate risk of bias.” The three moderate risk of bias studies, with a total of 98 patients, reported on severity of symptoms during challenge and on the ED. All three studies had a control group. Compared to the control group, improvement in severity of symptoms was observed during challenge in two out of the three studies and on the eliciting dose in one out of three. Only one study investigated the effect of birch pollen AIT on FA-QoL, showing that there was no significant difference between patients receiving subcutaneous immunotherapy or a placebo. Of the seven supportive studies, four had a control group and of those, three showed improvement on both severity of symptoms and ED. None of the supportive studies investigated the effect of the therapy on FA-QoL. Conclusion This systematic review shows that there is not enough evidence to draw firm conclusions about the effect of AIT on BPFA. Future research is warranted that uses robust clinical studies that include long-term effects, QoL, and multiple BPFA-related foods.